2016
DOI: 10.1097/ede.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Estimation of Marginal Absolute and Relative Associations in Case–Control Data

Abstract: Absolute and relative associations estimated from case-control data using a semiparametric targeted approach allow the scientific question to determine the analysis and avoid unwarranted parametric assumptions. A rare outcomes refinement provided more precise estimates than TMLE, and thus is well suited for the study of rare outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Case–control-weighted G-computation corrects for the case–control sampling by reweighting: cases are weighted according to the population prevalence of the outcome, and controls are weighted with (1-prevalence)/(control:case ratio). 32 , 33 The case–control-weighted G-computation formula is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Case–control-weighted G-computation corrects for the case–control sampling by reweighting: cases are weighted according to the population prevalence of the outcome, and controls are weighted with (1-prevalence)/(control:case ratio). 32 , 33 The case–control-weighted G-computation formula is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…In this context, Targeted Maximum Likelihood Estimation (TMLE) is one estimation option. Since the mid 2000's TMLE has been implemented successfully in numerous applications, initially for the effects of treatments or exposures at a single time point [1,2,3,4,5]. In recent years, an increasing body of work has dealt with the application of TMLE in longitudinal settings [6,7,8,9,10,11,12,13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The utilized HIPSS study also collected data on other STIs like Chlamydia trachomatis, Neisseria gonorrhoea, Mycoplasma genitalium, Trichomonas vaginalis, syphilis, hepatitis B, and human papillomavirus (HPV) infection. However, we selected HIV and HSV-2 because of their relatively high prevalence compared to other STIs, and the application of TMLE for rare outcomes is still in its infancy [20]. Moreover, previous reports [1], have shown that the associations of MMC with STIs other than HIV and HSV-2 were unreliable as the study was underpowered to detect rare STI outcomes.…”
Section: Discussionmentioning
confidence: 99%